2010
DOI: 10.1007/s00394-010-0157-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal transit and systemic metabolism of apple polyphenols

Abstract: The findings relating to the absorption, metabolism, and systemic availability of polyphenols in vivo should contribute to our understanding of their biological effects, and the characterization of newly formed metabolites should facilitate further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 60 publications
13
92
2
Order By: Relevance
“…These authors partially attributed the losses to the instability of some anthocyanins under alkaline conditions of the intestine. However, in a study also carried out on apples, catechins were degraded in an acidic stomach medium and posteriorly, their concentration increased in the presence of duodenal secretions because of a possible isomerization (Kahle et al, 2011). Finally, in other study published on the bioaccesibility of bioactives compounds of cacao, catechin and epicatechin contents augmented throughout digestion.…”
Section: Changes Experimented By Total Phenolic Content and Flavonoidmentioning
confidence: 98%
“…These authors partially attributed the losses to the instability of some anthocyanins under alkaline conditions of the intestine. However, in a study also carried out on apples, catechins were degraded in an acidic stomach medium and posteriorly, their concentration increased in the presence of duodenal secretions because of a possible isomerization (Kahle et al, 2011). Finally, in other study published on the bioaccesibility of bioactives compounds of cacao, catechin and epicatechin contents augmented throughout digestion.…”
Section: Changes Experimented By Total Phenolic Content and Flavonoidmentioning
confidence: 98%
“…In a recent study, it has been reported that most apple-derived polyphenols appear to be stable in the gastric medium, with the exception of procyanidin B 2 (a flavanol). However, anthocyanins were not studied within this investigation (Kahle et al, 2011).…”
Section: Fig 3 Reducing Antioxidant Capacity Assessed By the Frap Tmentioning
confidence: 99%
“…Non-targeted metabolite fingerprinting, using either NMR (17,19,21,28,29,31,33,35) or MS (20,(25)(26)(27) , and metabolite profiling using liquid chromatography MS (18,(22)(23)(24)28,30,32,34) have been used successfully for biomarker-lead discovery using urine samples from various study designs (Table 1). In acute food intervention studies (20,(22)(23)(24)(25)32) , participants were exposed to specific foods in known amounts and either postprandial urines sampled before the next meal or overnight or 24 h urines were collected. In other studies, participants were established on a specific diet for several days/weeks (17,19,21,28,33,35) or longer term (> 1 month) (18,31,34) before urine sampling.…”
Section: Dietary Exposure: Metabolite Fingerprinting: Ffq: Multivariamentioning
confidence: 99%
“…Postprandial urine composition reflects recent dietary exposure Table 1 lists several recent studies in which non-targeted metabolite fingerprinting or metabolite profiling has been used to discover dietary biomarkers in both acute and short-term food intervention studies (17,(19)(20)(21)(22)(23)(24)(25)28,32,33,35) . The basic design principles are illustrated in Fig.…”
Section: Dietary Exposure: Metabolite Fingerprinting: Ffq: Multivariamentioning
confidence: 99%